Assessment of knowledge, attitude and practices of personal and oral hygiene among undergraduate university students in Sulaimani city - Hasan, Akam Mustafa; Abdulqadir, Mardin Othman (Kurdistan Journal of Applied Research, 2017)
Poor hygiene performance and insufficient sanitary conditions assume real parts in the expanded weight of communicable diseases inside developing nations. Lack of resources such as hand washing materials, water and sanitation facilities may be essential factors why students do not wash their hands, also struggling of affordable toothpaste and absence of awareness regarding oral hygiene may be affected by improper cleaning teeth and tongue. This study was carried out to assess the knowledge, attitude and practices (KAP) of personal and oral hygiene among undergraduate university students in Sulaimani city /Iraq and evaluated the degree to which appropriate information of hygiene was related with individual hygiene character. This cross-sectional study was carried out among 1055 undergraduate students who were met via trained staff. Data comprised of cleanliness and hand washing practices, learning about sanitation, individual cleanliness qualities, nearness of gastrointestinal parasitic disease, oral and dental diseases including dental decay and bad breathes. University students with satisfactory information of legitimate personal and oral hygiene probably had clean clothes 68.8% (P value < 0.05), clean hair 72% (0.0001 P value), fingernail trimmed 139% (P value> 0.05), clean teeth 59.4% (P value <0.05), good mouth breath 57% (P value <0.05). Approximately 57.2% of students were delegated having sufficient information of legitimate cleanliness (P value <0.05). Most students preferred hand washing after defecation (96.5%) (P value <0.05), while 93.8% revealed utilizing shampoo. On the other hand 62.7% of contributors reported brushing their teeth before going to sleep (P value <0.05) and 74% of participants revealed cleaning their tongue sometimes (P value< 0.01). this study discovered underscore the requirement for more cleanliness training in universities; and give target confirm that may direct the improvement of far reaching personal, oral hygiene and health mediation programs in Sulaimani universities. Furthermore the effective usage of this study is probably going to significantly weaken the transmissible diseases.